KONSTRIBUSI PEMIKIRAN DJALALUDDIN THAIB TERHADAP PENDIDIKAN AGAMA ISLAM DI MINANGKABAU - Ismael, Fauzan; Sesmiarni, Zulfani (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of writing this article is to examine Djalaluddin Thain's contribution to Islamic Religious Education in Minangkabau. H. Djalaluddin Thaib is someone who only has a